Influenza virus binds its host cell using multiple dynamic interactions - Sieben, Christian (National Academy of Sciences, 2012)
Influenza virus belongs to a wide range of enveloped viruses. The major spike protein hemagglutinin binds sialic acid residues of glycoproteins and glycolipids with dissociation constants in the millimolar range [Sauter NK, et al. (1992) Biochemistry 31:9609–9621], indicating a multivalent binding mode. Here, we characterized the attachment of influenza virus to host cell receptors using three independent approaches. Optical tweezers and atomic force microscopy-based single-molecule force spectroscopy revealed very low interaction forces. Further, the observation of sequential unbinding events strongly suggests a multivalent binding mode between virus and cell membrane. Molecular dynamics simulations reveal a variety of unbinding pathways that indicate a highly dynamic interaction between HA and its receptor, allowing rationalization of influenza virus–cell binding quantitatively at the molecular level.